2006
DOI: 10.1111/j.1365-2036.2006.02996.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: the impact of gastro‐oesophageal reflux disease on work productivity

Abstract: SUMMARY BackgroundGastro-oesophageal reflux disease has wide-ranging effects on patients' lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
59
0
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(73 citation statements)
references
References 51 publications
4
59
0
10
Order By: Relevance
“…Multiple risk factors were identified for GERD; however, there is no general consensus regarding some risk factors particularly age, gender and alcohol consumption [10][11][12][13]. In one study in Iran the association between GERD and spouse GERD history was also reported [14].…”
Section: Introductionmentioning
confidence: 97%
“…Multiple risk factors were identified for GERD; however, there is no general consensus regarding some risk factors particularly age, gender and alcohol consumption [10][11][12][13]. In one study in Iran the association between GERD and spouse GERD history was also reported [14].…”
Section: Introductionmentioning
confidence: 97%
“…Gastroesophageal reflux disease (GERD) is the most common medical condition in Western societies, with 30% of adults suffering from heartburn at least once a month [1,2]. GERD is currently defined as a condition that develops when the reflux of gastric content causes troublesome symptoms and/or complications [3].…”
Section: Introductionmentioning
confidence: 99%
“…people with GERD have lower health-related quality-oflife scores than subjects with other chronic illnesses such as angina and heart failure [4,5].…”
mentioning
confidence: 99%